Multi-gene duplication removal in an engineered human cellular MECP2 duplication syndrome model with an IRAK1-MECP2 duplication - Samar Z. Rizvi; Wing Suen Chan; Eleonora Maino; Sydney Steiman; Georgiana Forguson; Maya Klepfish; Ronald D. Cohn; Evgueni A. Ivakine (Molecular Therapy: Nucleic Acids)
Recent progress in genome editing technologies has catalyzed the generation of sophisticated cell models; however, the precise modeling of copy-number variation (CNV) diseases remains a significant challenge despite their substantial prevalence in the human population. To overcome this barrier, we have explored the utility of HAP1 cells for the accurate modeling of disease genomes with large structural variants. As an example, this study details the strategy to generate a novel cell line that serves as a model for the neurological disorder methyl CpG binding protein 2 (MECP2) duplication syndrome (MDS), featuring the critical duplication of both the MECP2 and IRAK1 genes. This model faithfully recapitulates MDS genomic rearrangement, allowing for the mechanistic study of gene overexpression and the development of therapeutic interventions. Employing a single-guide RNA (gRNA) CRISPR-Cas9 strategy, we successfully excised the duplicated genomic segment, notably halving both MECP2 and IRAK1 expression levels. The evidence establishes our model as a crucial tool for research into MDS. Furthermore, the outlined workflow is readily adaptable to model other CNV disorders and subsequently test genomic and pharmacological interventions.